Analisis Manajemen Resiko Penggunaan Aplikasi Youtube Pada Anak Usia Dini - Amanda Eka Febrianisa; Nurul Rizak Imanuloh; Rahmawati Desi Tri Wulandari; Sofa Marwati; Tiara Putri Maharani (Prosiding Seminar Nasional Teknologi Informasi dan Bisnis, 2023)
Excessive use of the YouTube application by young children should be avoided so as not to affect children's development. The purpose of this study is to analyze the role of parents in risk management for implementing digital parenting so that young children are not addicted to opening the YouTube application. This research is a descriptive qualitative research. The subjects of this study were parents who had children between the ages of 8 and 10 who were identified through purposive random sampling. Information was collected through interview techniques. The collected qualitative data was then analyzed using data triangulation techniques. The results of the study show that the role of parents in implementing digital education to prevent early childhood risks in opening the Yotube application is as follows: Control of content viewed, duration of YouTube viewing, family support, family environment, YouTube is used by children, YouTube should be kids and Youtube as a learning tool and media. The videos they watch are not immoral and take up screen time. Digital parenting is a method that can be used to prevent addiction to opening the YouTube application in young children